Emigration and colony budding behaviour of the black crazy ant, Paratrechina longicornis latreille (Hymenoptera: Formicidae) - Nur Syahida Wadhihah Kamarudin,; Nur Adila Kamaruddin,; Norasmah Basari, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The existence of the house infesting ants not only brings nuisance to humans, but they could also infest foodstuffs which can lead to food poisoning. They may emigrate and even split from the main colony into two or more colonies when disturbed. To produce highly effective control products, it is essential to understand how fast the ant colonies emigrate and how they divide their colonies when after disturbed. The aims of our study were to determine the emigration time and to identify the number of new nests emerging from a single colony. In the first experiment, one artificial nest was placed in front of the old nest at 40 cm distance for emigration method. In the second experiment, three new nests were provided 40 cm in front of the old nest to investigate the budding behaviour. Results revealed that the Black Crazy Ant, Paratrechina longicornis colonies completed emigration time in about one hour and small colonies with minimum as 38 workers can split into two new nests after destruction of the old nest. This study provides new information and understanding of the household ant behaviour which is essential in pest management.